(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article is about the process of literary and theoretical study of the modern Kazakh prose. The experience of using typological, hermeneutic techniques and methods for determining the evolution of genre and issues of poetics, art and the specific features of modern Kazakh literature was analyzed. The relevance of the scientific work on literary and theoretical study of the modern Kazakh prose is noted. The novelty of methodological approaches of literary definition of new aesthetic facets and poetic forms in the literary process of modern Kazakh literature of 1970-1980 are assessed. On the basis of the most important scientific works main achievements of estetic concept analysis on the theory and aesthetics of literature are identified. Thus the proсess of scientific and theoretical development of one of the most difficult direction of Kazakh literature, literary theory is traced.